PERILAKU STICKY COST PADA PERUSAHAAN PERDAGANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Magdalena Nany; Lyna Lyna; Evi Haloho (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2022)
This study aims to present empirical evidences of sticky cost behavior indications on selling costs, general and administrative costs and cost of goods sold in trading companies using sticky cost model testing. The hypotheses in this study are H1: The amount of the increase in selling costs when net sales rise higher than the amount of the decrease in selling costs when net sales fall. H2: The amount of the increase in general and administrative costs when net sales rise higher than the amount of the decrease in general and administrative costs when net sales fall. H3: The amount of increase in cost of goods sold when net sales rise higher than the amount of decrease in cost of goods sold when net sales fall. This study uses secondary data This study uses secondary data from trading companies listed in Indonesia Stock Exchange period of 2018-2019. Data were analyzed by multiple regression analysis. The results of this study identify that not all hypotheses are accepted. Hypothesis 1 is not supported by research results or the selling costs are not sticky. Hypothesis 2 is not supported by research results or the general and administrative costs are not sticky. Hypothesis 3 is supported by the research results or the cost of goods sold is sticky. Keywords: sticky cost, selling costs, general and administrative costs, cost of goods sold